ANALYSIS OF PRODUCER BEHAVIOR CV. BLJ ACCORDING TO THE PRINCIPLES OF PRODUCTION IN ISLAM - Kholishoh, Ziadatun (Pedagogic Research-Applied Literacy Journal, 2025)
The theory of producer behavior in an Islamic perspective is a science that studies human economic behavior in which behavior is regulated based on Islam. This study aims to determine the behavior of manufacturers of CV. Bintang Laut Jaya in producing halal ingredients, especially the behavior of CV producers. Bintang Laut Jaya according to the principles of production in Islam for the sake of achieving benefit, the research method used is descriptive qualitative by conducting observations and interviews with CV producers. Bintang Laut Jaya in Tuban, East Java. The results of the study are the motivation of business owners in carrying out production activities is to work and of course seek profits accompanied by benefits for the community, the behavior of producers CV. Bintang Laut Jaya is in accordance with the principles of production in Islam, namely the principles of monotheism, humanity, justice, responsibility, but not in accordance with the principles of virtue